Isolation and characterization of related cDNA clones encoding skeletal muscle beta-tropomyosin and a low-molecular-weight nonmuscle tropomyosin isoform. - Bradac, J A (1989)
We have isolated and characterized cDNA clones from chicken cDNA libraries derived from skeletal muscle, body wall, and cultured fibroblasts. A clone isolated from a skeletal muscle cDNA library contains the complete protein-coding sequence of the 284-amino-acid skeletal muscle beta-tropomyosin together with 72 bases of 5' untranslated sequence and nearly the entire 3' untranslated region (about 660 bases), lacking only the last 4 bases and the poly(A) tail. A second clone, isolated from the fibroblast cDNA library, contains the complete protein-coding sequence of a 248-amino-acid fibroblast tropomyosin together with 77 bases of 5' untranslated sequence and 235 bases of 3' untranslated sequence through the poly(A) tract. The derived amino acid sequence from this clone exhibits only 82% homology with rat fibroblast tropomyosin 4 and 80% homology with human fibroblast tropomyosin TM30nm, indicating that this clone encodes a third 248-amino-acid tropomyosin isoform class. The protein product of this mRNA is fibroblast tropomyosin 3b, one of two low-molecular-weight isoforms expressed in chicken fibroblast cultures. Comparing the sequences of the skeletal muscle and fibroblast cDNAs with a previously characterized clone which encodes the smooth muscle alpha-tropomyosin reveals two regions of absolute homology, suggesting that these three clones were derived from the same gene by alternative RNA splicing.